Durable Polymer Everolimus-Eluting Stents Versus Free Polymer Sirolimus-Eluting Stents - الخيّر إياس (Latakia University Journal -Medical Sciences Series, 2023)
With the evolution of medical engineering and the emergence of the new generation of drug-eluting stents, there is need to carry out new studies to prove the optimal management. In our study, the results of implanting stents of cobalt-chromium with free polymer and stents of cobalt-chromium with durable polymer. It included 250 patients admitted to Tishreen University Hospital, 150 patients with free polymer stents , and 100 with durable stents. And the results are similar between the two group. From the point of view of cardiac death p = 0.81 and myocardial infarction p = 0.5 and the need for revascularization p = 0.38.